Single-mode fiber tip for enhancing optical trapping of silica particles - Nik Mahmud, Nik Noor Haryatul Eleena; Lim, Fung Keat; Awang, Noor Azura; Joshi, Prakash; Wan Ahmad Kamil, Wan Maryam (elsevier, 2025)
Optical fiber has attracted significant interest in particle trapping due to its efficiency and versatility in particle manipulation. This paper presents a novel method for trapping silica gel particles using single-mode fiber tips specifically designed to attract the particles. Silica gel samples with a diameter of 241 µm were utilized as the trapping sample and the input power in fiber varied from 14.1 mW to 56.5 mW. Experimentally, the trajectory of the silica gel was analysed using Tracker Software and Digital Microscope. Additionally, a numerical simulation was conducted to validate the optimal trapping conditions. A comparative analysis of experimental and simulation results reveals that the most efficient optical trapping force lies at pump power 26.8 mW with 0.35 s time taken for silica gel to trap. These findings confirm the potential of single-mode fiber tips for precise and effective trapping of particles under optimized power conditions.